Uncoupling conformational change from GTP hydrolysis in a heterotrimeric G protein α-subunit - Thomas, Celestine J. (National Academy of Sciences, 2004)
Heterotrimeric G protein α (Gα) subunits possess intrinsic GTPase activity that leads to functional deactivation with a rate constant of ≈2 min(-1) at 30°C. GTP hydrolysis causes conformational changes in three regions of Gα, including Switch I and Switch II. Mutation of G202→A in Switch II of Gα(i1) accelerates the rates of both GTP hydrolysis and conformational change, which is measured by the loss of fluorescence from Trp-211 in Switch II. Mutation of K180→P in Switch I increases the rate of conformational change but decreases the GTPase rate, which causes transient but substantial accumulation of a low-fluorescence Gα(i1)·GTP species. Isothermal titration calorimetric analysis of the binding of (G202A)Gα(i1) and (K180P)Gα(i1) to the GTPase-activating protein RGS4 indicates that the G202A mutation stabilizes the pretransition state-like conformation of Gα(i1) that is mimicked by the complex of Gα(i1) with GDP and magnesium fluoroaluminate, whereas the K180P mutation destabilizes this state. The crystal structures of (K180P)Gα(i1) bound to a slowly hydrolyzable GTP analog, and the GDP·magnesium fluoroaluminate complex provide evidence that the Mg(2+) binding site is destabilized and that Switch I is torsionally restrained by the K180P mutation. The data are consistent with a catalytic mechanism for Gα in which major conformational transitions in Switch I and Switch II are obligate events that precede the bond-breaking step in GTP hydrolysis. In (K180P)Gα(i1), the two events are decoupled kinetically, whereas in the native protein they are concerted.